Wu zui bianhu : Di sanji, da jieju - Zhang, Haisheng (Beijing : Zhongguo you yi chu ban gong si, 2017)
$1!Ci'CU'Y4![m'Ms!+:'PA!C!!5w'7a'2A'^]'9#!?b!Oe'Ms'2A!C!!=b'<Q!0P'43!?u!+8';?'^M'IQ!5'-~j!C~!M"!WV!5_!0d!?}'If!R2'[a'YH!M"!:o!5-!+8!0q'1s!0w!=b'<Q!M"!X3!<u!+8!N0'K)'Ms!MJ!1='Y?'A|'NI'^K!M"'2s!DB!+8!0w'KG'8J'\W!4x!M"!?z!G*'QN'YH!F#'RB!+8!0w!<x!0&!I$!I[!M"'[a'Y$'IQ-~j!R_!C(!_R!+8!0q'1s';C!F#'RB!M"'8;"at!5w!1?'IQ!=b'<Q!M"'Ym!0|!>n!0n!0d'44!:}!+3s
The book tells: Concise and Roger partnered to set up Jieming Law Firm, a lawsuit specifically defending the accused who was acquitted. From the perspective of lawyers, they cracked a seemingly convincing murder case to restore the scene. The tactics of maintaining justice and the fierce debate in the court are the witnesses, and their persistence in justice and their sense of responsibility as lawyers are moving.
Keywords: Chinese fiction; Detective and mystery fiction